Parasitic infection of the appendix as a cause of acute appendicitis - da Silva, Danielle Fernandes; da Silva, Reinaldo Jose; Silva, Marcia Guimarães da [UNESP]; Sartorelli, Alesso Cervantes; Rodrigues, Maria Aparecida Marchesan [UNESP] (Springer, 2007)
The association between parasitic infection of the appendix and acute appendicitis has been widely investigated. The aim of this retrospective study was to evaluate the prevalence of parasitic infection of the appendix in a tropical area at southeast Brazil and to assess its possible relation to acute appendicitis in surgically removed appendices. of the 1,600 appendectomies performed during a 10-year period, 24 (1.5%) were found to have helminths within the appendix. Enterobius vermicularis was observed in 23 of the 24 specimens (95.8%), and Taenia sp. was detected in only one case. Sixteen patients (66.7%) were less than 10 years old; 15 patients were male and nine female; 21 patients were white, and three were nonwhites. Pathologic analysis disclosed acute neutrophilic inflammation in the appendix wall in 12 of the 24 specimens and lymphoid hyperplasia in 10 of the 24 appendices. Gangrenous appendicitis was diagnosed in three cases, and peritonitis was found in 11 of the 24 infected appendices. The results of the present study indicate that E. vermicularis is the commonest worm found in the appendix and that its presence can cause pathologic changes ranging from lymphoid hyperplasia to acute phlegmonous inflammation with life-threatening complications like gangrene and peritonitis.